Pengaruh Kepuasan Karir terhadap Kesuksesan Karir melalui Komitmen Karir Studi pada PT Aneka Gas Industri Region V Sidoarjo - AMIRUDDIN, MOHAMAD (Jurnal Ilmu Manajemen (JIM), 2018)
Every individual would want to have a career owned has increased in accordance with what is desired. Because the career is one of the liaison between individuals with organizations in the company. Many of them usually do early in youth, because in each individual wants to have a sense of happiness and success for the future. Practice education and training in accordance with the ability and capacity which when followed should be well planned for later when in turn can be promoted and moved from a position to a higher position and higher responsibilities. So with that need memeperhatikan career desired by each individual. The purpose of this research is to know and analyze the influence of career satisfaction toward career success through career commitment study at PT Aneka Gas Industri Region V Sidoarjo. This research is explanatory research, using quantitative approach with total sample 37 employees. Measurers used interviews, questionnaires, observation, and documentation. Data analysis using Partial Least Square (PLS) technique with the help of SmartPLS 3.0 and Statistical Package for the Social Science (SPSS) software. The measurement scale used is Likert Scale. The results showed that career satisfaction has a positive effect on career commitment, career commitment has a positive effect on career success, career satisfaction has a positive effect on career success, and career satisfaction has a positive effect on career success through career commitment. Keywords: career satisfaction, career commitment, career success